Ground sloths and humans in southern Fuego-Patagonia: taphonomy and archaeology - Borrero, Luis Alberto (2012)
An evaluation of Late Pleistocene interactions between ground sloths and humans in the Fuego-Patagonia of Chile and Argentina is presented. Aspects of ground sloth taphonomy are explored,particularly the difficulties of using cut-mark and breakage evidence to recognize humanexploitation. Selective transport of large animal bones is also reviewed in regards to its use as amarker of human exploitation of ground sloths. An evaluation of the relevant archaeological andpaleontological records for the individual taxon Mylodon sp. is presented. It is concluded that thereis little to no evidence for active human hunting of ground sloths and that scavenging is the onlyform of interaction that can be defended.